Clinic screening for adverse childhood experiences in people living with HIV to Improve Care Delivery. Issue 9 (2nd September 2022) - Anand, Priyanka; Wilson, Jennifer; Carter, Bryce; Bronstein, Abby; Schwartz, Alexis; Harrington, Brittney; Adams, Tracey; Saine, M. Elle; Norris, Anne; Metzger, David; Short, William R.; Torgersen, Jessie
ABSTRACT: Adverse childhood experiences (ACEs) are associated with negative health outcomes; however, screening for ACEs is not routinely performed among people living with HIV (PLWH). We conducted a single-center, cross-sectional pilot study to define the (1) prevalence of ACEs in PLWH and (2) acceptability of ACEs screening in routine out-patient clinical care. One hundred participants completed screening: median age of participants was 49 years (interquartile range: 38.5-59.5), 73% male, 66% Non-Hispanic Black/African American, and 47% gay/lesbian. Clinically significant ACEs score, defined as ≥4, was reported in 51%. High ACEs score was more common among participants <50 years old (64.7% vs. 36.7%; p < 0.01), but the prevalence of ACEs ≥4 did not differ by gender, race, ethnicity, or sexual orientation. Among participants with ≥4 ACEs, 44.4% screened negative on both PHQ-9 and PC-PTSD screens. The majority of participants (89%) reported a positive experience with ACEs screening. The prevalence of clinically significant ACEs in this clinic population of PLWH was more than twice that reported in the general population. Routine ACEs screening can improve delivery of trauma-informed care in the HIV primary care setting.